Spark plasma assisted carbothermal reduction-nitridation synthesis of (Ti, W, Mo)(C, N)-(Ni, Co) powders. Issue 17 (1st December 2017) - Li, Hui; Xiang, Daoping; Cao, Yue; Zhao, Shuning; Tu, Guopeng
Abstract: Ultrafine (Ti, W, Mo)(C, N)-(Ni, Co) cermet powders were rapidly synthesized from various metal oxides, mainly anatase-TiO2, by spark plasma assisted carbothermal reduction-nitridation (SPCRN) at low temperature. The phase evolution of the SPCRN reaction was investigated using X-ray diffraction (XRD) and the microstructure of the product powders was observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). NiO, Co3 O4 and MoO3 were converted to Ni, Co and Mo2 C by CR reaction at temperatures below 900 °C. WO3 was successively transformed from W2 C to WC by CR reaction up to 1100 °C. Finally, at up to 1350 °C, (Ti, W, Mo)(C, N) formed into the sequence of TiO2, Ti4 O7, Ti3 O5, Ti(O, N), Ti(C, N), (Ti, W)(C, N) and (Ti, W, Mo)(C, N). The crystal structure of (Ti, W, Mo)(C, N)-(Ni, Co) cermet powders was analyzed by the Rietveld method and transmission electron microscopy (TEM). The findings demonstrated that the pure (Ti, W, Mo)(C, N)-(Ni, Co) cermet powders with grain size of below 0.5 µm were synthesized from metal oxides by SPCRN reaction at 1400 °C for 10 min.